Pendekatan Keagamaan Mediator Terhadap Para Pihak Dalam Perkara Perceraian di Pengadilan Agama - Karmawan Karmawan (Kopertais Wilayah I DKI Jakarta dan Banten, 2019)
The religious knowledge possessed by the mediator becomes the basis for the case in the religious court, the religious court provides space for the mediator to improve his ability so that the mediated case is not in the form of a decision from a panel of judges but in the form of a peace deed. The mediator uses a religious approach to be understood by the parties considering separating. Because the religious approach is considered more rational in the family problem back to the teachings of Islam, not disagree with each other. The mediator of the religious court provides religious knowledge in the form of advice to the parties in the event of a divorce which is certainly sacrificed by the problems of the position of husband and wife, issues of property and status of children who are victims of the separation of their parents